2013
DOI: 10.1111/jne.12058
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Hypothyroxinaemia Induced by Maternal Mild Iodine Deficiency Delays Hippocampal Axonal Growth in the Rat Offspring

Abstract: Iodine is essential for the biosynthesis of thyroid hormones, including triiodothyronine and thyroxine. Thyroid hormones are important for central nervous system development. Mild maternal iodine deficiency (ID)-induced hypothyroxinaemia causes neurological deficits and mental retardation of the foetus. However, the detailed mechanism underlying these deficits is still largely unknown. Given that the growth-associated protein of 43 kDa (GAP-43), semaphorin 3A (Sema3A) and the glycogen synthase kinase 3β (GSK3β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
(77 reference statements)
1
23
0
1
Order By: Relevance
“…In yet another study, rodents were treated with an iodinedeficient diet and deionized water containing various doses of iodine in order to establish a mildly iodine-deficient animal model [17]. This research group found that the development of hypothyroxinemia in response to mild iodine deficiency led to impairments of long-term potentiation (LTP) induced by high-frequency stimulation, strongly suggesting irreversible injury to the hippocampus [98].…”
Section: Hippocampusmentioning
confidence: 98%
See 1 more Smart Citation
“…In yet another study, rodents were treated with an iodinedeficient diet and deionized water containing various doses of iodine in order to establish a mildly iodine-deficient animal model [17]. This research group found that the development of hypothyroxinemia in response to mild iodine deficiency led to impairments of long-term potentiation (LTP) induced by high-frequency stimulation, strongly suggesting irreversible injury to the hippocampus [98].…”
Section: Hippocampusmentioning
confidence: 98%
“…The successful establishment of rodent models of hypothyroxinemia has shown structural and functional alterations in pups' various brain regions, especially the hippocampus and cerebellum. The abnormal development of such brain regions is closely related to cognitive and psychomotor dysfunction [16][17][18]. This review summarizes the existing evidence concerning the relationship between maternal hypothyroxinemia and consequences of neurodevelopment in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aberrant cytoarchitecture seen in the above studies, maternal hypothyroxinemia in animal models has been associated with a number of other structural changes, including limited dendritic growth of cerebellar Purkinje cells (15), delayed hippocampal axonal development (16) and alterations of glutamergic synapses (17). Functional consequences of maternal hypothyroxinemia in the fetus have been impaired spatial learning (17), impairment of long-term potentiation in the hippocampus (17) and increased frequency of abnormal response (wild runs or seizures) to audiogenic stimuli (13).…”
Section: Animal Models Of Imhmentioning
confidence: 99%
“…In the rat, embryonic day 0 (E0) is the day of conception; birth occurs at E21-E22, while fetal thyroid is functional at E17. [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Neurogenesis and migration in the rat occur over 10 days, between E11 and E21, and therefore a period of 3 days in rat brain development corresponds roughly to 37-38 days in humans (13).…”
Section: Animal Models Of Imhmentioning
confidence: 99%
See 1 more Smart Citation